A Study on Impact of Merger & Demerger of Banks in India with Special Reference to Public & Private Banks: An Investigation into the Impact of Bank Mergers and Demergers on the Financial Performance of Public and Private Banks in India (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research aimed to examine how bank Merger Demerger in India have affected theoperations and finances of the bank. It has also been determined how mergers affect the wealth ofacquiring banks in the short and long term. Public and private sector acquirer banks' performance aftermergers has also been examined. This investigation relies on secondary sources of information.Statistics such as the mean, standard deviation, ratio analysis, paired sample t-test, Shapiro-Wilk test,Corrado Rank test, DEA analysis, EVA analysis, and Event Study analysis have been used to examinethe data. Our research compared the financial health of both firms before and after their 2015-16demerger. To determine whether or not the demergers had a material effect on the financial performanceof the firms involved, a sample paired t-test was conducted. After using the aforementioned statisticalmethod, As stand-ins for actual financial performance, we considered such metrics as return oninvestment (ROI), return on net worth (RONW), and earnings per share (EPS).